Letter - Winstanley, E.
030-0020-001 Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. 87 Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. OUR REFERENCE EXPORT 1733 ST/HP. YOUR REFERENCE 20th October, 1938. The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. [shorthand] case number Dear Sirs, Up to the present, we do not appear to have received your marking and numbering instructions for the goods we have on order on your account for shipment to Spain, via Rouen. It is imperative that we issue our shipping instructions tomorrow, and trust, therefore, that you will either let us have the information by telephone or telegraph tomorrow. We shall also require to know at your earliest convenience, the name and address of consignee, although we assume that this will be Sr. Enrique Santiago, Comite Espagnol del Fondo Solidaridad Internacional, Aragon 300, Barcelona, as formerly. Thanking you in anticipation, we remain, Yours faithfully E. Winstanley Export Department. 292/946/30/20